Building a Bridge Between NMDAR-Mediated Excitotoxicity and Mitochondrial Dysfunction in Chronic and Acute Diseases - Mira, Rodrigo G.; Cerpa, Waldo (My University, 2021)
Glutamate is the major excitatory neurotransmitter in the brain, and it is widely accepted to play a role in synaptic plasticity and excitotoxic cell death. Glutamate binds to several receptors, including ionotropicN-methyl-d-Aspartate receptor (NMDAR), which is essential in synaptic plasticity and excitotoxicity. This receptor is a calcium channel that is located in synaptic and extrasynaptic sites, triggering different signalling cascades in each case. The calcium entry through extrasynaptic NMDARs is linked to calcium overload in the mitochondria in neurons in vitro. The mitochondria, besides their role in ATP production in the cell, participate in calcium homeostasis, acting as a buffering organelle. Disruption of mitochondrial calcium homeostasis has been linked to neuronal death either by triggering apoptosis or driven by the opening of the mitochondrial transition pore. These cell-death mechanisms contribute to the pathophysiology of diverse diseases such as neurodegenerative Alzheimer's disease or Parkinson's disease, and acute neuropathological conditions such as stroke or traumatic brain injury. In this review, we will address the available evidence that positions the mitochondria as an essential organelle in the control of calcium-mediated toxicity, highlighting its role from the perspective of specific NMDAR signalling microdomains at the level of the central synapse.
Keywords: nmdar; calcium; mitochondria; excitotoxicity